2020
DOI: 10.1128/aac.01273-20
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Investigation of Resistance Evolution to Common Antibiotics Reveals Conserved Collateral Responses across Common Human Pathogens

Abstract: As drug resistance continues to grow, treatment strategies that turn resistance into a disadvantage for the organism will increasingly be relied upon to treat infections and to slow the rate of multidrug resistance. The majority of work in this area has investigated how resistance evolution toward a single antibiotic effects a specific organism's collateral response to a wide variety of antibiotics. Results of these studies have been used to identify networks of drugs which can be used to drive resistance in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 67 publications
1
2
0
Order By: Relevance
“…Существует предположение, что изменение клеточного дыхания за счёт изменения работы электрон-транспортной цепи влияет на электрический потенциал мембраны, что в свою очередь, влияет на пенетрацию аминогликозидов внутрь клетки [25]. Мутации в гене fusA, обуславливают устойчивость к фузидиевой кислоте, а также к аминогликозидам [26]. В настоящем исследовании только у одного штамма была выявлена мутация в fusA, без изменений чувствительности к фузидиевой кислоте.…”
Section: экспериментальные статьиunclassified
“…Существует предположение, что изменение клеточного дыхания за счёт изменения работы электрон-транспортной цепи влияет на электрический потенциал мембраны, что в свою очередь, влияет на пенетрацию аминогликозидов внутрь клетки [25]. Мутации в гене fusA, обуславливают устойчивость к фузидиевой кислоте, а также к аминогликозидам [26]. В настоящем исследовании только у одного штамма была выявлена мутация в fusA, без изменений чувствительности к фузидиевой кислоте.…”
Section: экспериментальные статьиunclassified
“…The evolutionary conservation of collateral responses to five clinically relevant antibiotics (cefepime, ciprofloxacin, gentamicin, meropenem, and tetracycline) across species, particularly within the ESKAPE pathogens, was investigated [60]. This study identified 14 instances of universal cross-resistance that accounted for 80% of all the collateral responses and two global collateral sensitivity relationships (cefepime and gentamicin pair and ciprofloxacin and gentamicin pair) among the evolved lineages [60]. Although the genetic basis for the collateral sensitivity was unclear, genomic analyses revealed divergent and conserved evolutionary trajectories, suggesting that collateral responses may be preserved across species for the selected drugs [60].…”
Section: Impact Of Multidrug Combinations On Amr Evolutionmentioning
confidence: 99%
“…This study identified 14 instances of universal cross-resistance that accounted for 80% of all the collateral responses and two global collateral sensitivity relationships (cefepime and gentamicin pair and ciprofloxacin and gentamicin pair) among the evolved lineages [60]. Although the genetic basis for the collateral sensitivity was unclear, genomic analyses revealed divergent and conserved evolutionary trajectories, suggesting that collateral responses may be preserved across species for the selected drugs [60].…”
Section: Impact Of Multidrug Combinations On Amr Evolutionmentioning
confidence: 99%
“…It was demonstrated [34] that when a strain of E. faecium was exposed to stress events, such as sub-lethal concentrations of NaCl, it showed an improved adaptation to a second stress episodeat increased heat levels. The resistance of individual isolates is supposed to be improved, following that one of the bacterial population [35]. However, isolates-outliers with decreased resistance compared to their corresponding populations can be detected because of sample storage at -80°C, before use.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%